The TGF-beta — SMAD pathway is inactivated in cronic lymphocytic leukemia cells - Matveeva, A.; Kovalevska, L.; Kholodnyuk, I.; Ivanivskaya, T.; Kashuba, E. (Experimental Oncology, 2017)
Aim: To study the status of the tumor growth factor beta (TGFB) pathway in chronic lymphocytic leukemia (CLL) cells and to uncover molecular details underlying CLL cell genesis. Objects and Methods: The study was conducted on peripheral blood samples of patients with CLL using the following methods: RNA isolation, analysis of expression of transcription factors using RT2 profiler assay, bioinformatics analysis of publicly available data bases on expression. Results: We have shown that the TGFB — SMAD canonical pathway is not active in CLL cells. SMAD-responsive genes, such as BCL2L1 (BCL-XL), CCND2 (Cyclin D2), and MYC, are down-regulated in CLL cells compared with peripheral blood B cells of healthy donors. Conclusions: The TGFB-mediated signaling is not active in CLL cells due to low (or absent) expression of SMAD1, -4, -5, -9, and ATF-3. Expression and phosphorylation status of SMAD2 and -3 should be further elucidated in the future studies.